CLANDESTINE MEMORIES: FROM COMBAT TRENCHES TO MEMORY PLACES OF SHINING PATH IN CEMETERIES OF THE DEPARTMENT OF LIMA - Estrada Moreno, Flavio Antonio (2015)
Since 1986 members of Shining Path structured fifteen places of memory in various cemeteries of the department of Lima. A constant conflict over two decades in which colors, symbols and phrases were used to keep those clandestine memories constantly renewed.